Islamic Marketing Strategy in Developing Crab Meat Business: A Case Study of CV. Perjuangan 7703 in Waruduwur Village, Cirebon Regency, Indonesia - Gama Pratama; Siti Amanah (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2026)
This study aims to analyze the implementation of Islamic marketing strategies in developing a crab meat business at CV. Perjuangan 7703 located in Waruduwur Village, Cirebon Regency, Indonesia. This research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation, and analyzed using descriptive analysis techniques. The findings reveal that the company has implemented marketing strategies in accordance with the 7P marketing mix framework, including product, price, place, promotion, people, process, and physical evidence, which effectively support business development. Furthermore, the application of Islamic marketing principles—rabbaniyah (theocentric), akhlaqiyah (ethical), al-waqi’iyyah (realistic), and insaniyah (humanistic)—has enhanced transparency, trust, and direction in marketing practices compared to conventional approaches. Despite several challenges in sustaining the business, the company has adopted appropriate problem-solving strategies that enable it to maintain and develop its operations. This study highlights that integrating Islamic marketing values into business practices can contribute positively to sustainable business development, particularly in small and medium enterprises in the fisheries sector.